The Consumer Hotel Selection Factors Analysis - Milawati Milawati; Diyan Putranto; Adi Sopyan; Anindita Gayatri; Barliani Dewi Setyawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study's objective is to investigate the role that factors such as service quality, trustworthiness, and amenities play in determining which guests choose to stay at Hotel XYZ in Jakarta. The research sample was comprised of 215 individuals who were chosen using the process of accidental sampling. The data analysis was carried out with the assistance of SPSS version 25's statistical analysis software, and it made use of both multiple regression and hypothesis testing. The findings of the research indicate that the quality of customer service, level of trust, and amenities offered at a hotel all have a significant impact on the decision-making process involved in selecting a guest room, with individual significance levels ranging from 0.000 to 0.05. In the f-test study, all three of these variables were found to have a significant influence on the decision-making process for selecting a guest hotel simultaneously.